2017
DOI: 10.1128/aac.02740-16
|View full text |Cite
|
Sign up to set email alerts
|

VraR Binding to the Promoter Region of agr Inhibits Its Function in Vancomycin-Intermediate Staphylococcus aureus (VISA) and Heterogeneous VISA

Abstract: Acquisition of vancomycin resistance in Staphylococcus aureus is often accompanied by a reduction in virulence, but the mechanisms underlying this change remain unclear. The present study was undertaken to investigate this process in a clinical heterogeneous vancomycin-intermediate S. aureus (hVISA) strain, 10827; an hVISA reference strain, Mu3; and a VISA reference strain, Mu50, along with their respective series of vancomycin-induced resistant strains. In these strains, increasing MICs of vancomycin were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…aureus virulence by binding the P2-P3 intergenic region of the agr promoter, indicating that when S. aureus is subject to vancomycin induction, VraR binds and inhibits the function of the Agr quorum sensing system, causing reductions in the virulence of VISA/hVISA strains (42, 43). Given our previous findings revealing (i) that VraSR is a key factor during DAP resistance and (ii) the defective expression of agr found in CB1634, we postulated that VraSR may transcriptionally regulate agr expression in CB1634.…”
Section: Resultsmentioning
confidence: 99%
“…aureus virulence by binding the P2-P3 intergenic region of the agr promoter, indicating that when S. aureus is subject to vancomycin induction, VraR binds and inhibits the function of the Agr quorum sensing system, causing reductions in the virulence of VISA/hVISA strains (42, 43). Given our previous findings revealing (i) that VraSR is a key factor during DAP resistance and (ii) the defective expression of agr found in CB1634, we postulated that VraSR may transcriptionally regulate agr expression in CB1634.…”
Section: Resultsmentioning
confidence: 99%
“…agr -defective strains have been associated with the development of vancomycin tolerance ( 39 , 40 ); however, agr dysfunction is associated with only small reductions in killing that are apparent only with long-term, time-kill experiments ( 41 , 42 ). Consequently, we focused on several agents known to be rapid, concentration-dependent killers of S. aureus (gentamicin, ciprofloxacin, and daptomycin).…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of vancomycin resistance in S. aureus is often accompanied by reduced virulence. A recent study found that VraSR directly regulated the function of the Agr quorum-sensing system and, thus, inhibited virulence in S. aureus (53). However, our data showed that vraSR SS expression was significantly higher in vivo than in vitro, which prompted us to consider its potential roles in pathogenesis.…”
Section: Discussionmentioning
confidence: 54%